Diagnosis dan Tatalaksana Otitis Media Supuratif Kronik - Rizqiani Astrid Nasution; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Chronic suppurative otitis media or also known as CSOM is a chronic inflammation or infection of the middle ear with a perforation of the tympanic membrane accompanied by or without discharge in the ear canal for at least 2-6 weeks. Chronic suppurative otitis media may start as otitis media with progressively worsening tympanic membrane perforation. The presence of cholesteatoma, namely the keratinized squamous epithelium in the middle ear can worsen the patient's condition to the point of complications. The diagnosis of chronic suppurative otitis media includes anamnesis, physical examination, and supporting examinations. In the anamnesis, the patient experiences symptoms such as decreased hearing function, discharge from the ear canal, tinnitus, a feeling of fullness in the ear, and can be accompanied by otalgia and high fever which indicates complications. The physical examination was carried out by examining the ear canal, examining the middle ear, and examining the hearing test in the form of a tuning test consisting of a Rinne test, Weber test, and Schwabach test, as well as a whispered voice test. In supporting examination of chronic suppurative otitis media, pure tone audiometry, Brainstem Evoked Response Audiometry (BERA) and otomicroscopy were performed. Management of chronic suppurative otitis media consists of non-operative management and operative management. Non-operative management is carried out with an aural toilet, administration of topical and systemic antibiotics, and education. Operative management is in the form of surgery consisting of myringoplasty, tympanoplasty, and mastoidectomy. Operative management is carried out if the patient with chronic suppurative otitis media is not responsive to topical or systemic medical therapy with appropriate aural toilet.